LITERATURE REVIEW: The Effectiveness of Educational Media in Building Positive Character among Students - Astri Amelia; Juhana, Agus (SUKMA: Jurnal Pendidikan, 2025)
Character education in the digital era is essential for shaping students' personalities. Through educational media, character teaching can be more creative and interactive. This study aims to explore effective types of educational media for fostering positive character in students and to evaluate implementation challenges. Using a Systematic Literature Review (SLR) and data mining with the Publish or Perish software, 30 articles met the inclusion criteria for analysis with keywords: (effectiveness) AND ("character education" OR "positive character development") AND ("educational media" OR "technology in education") AND (student). Findings identify types of media supporting character education, assess their effectiveness, and outline challenges in application. Study limitations include a focus on English articles, certain media types, and limited field studies. Future research should explore further integration of technology in character education and conduct field studies to understand implementation.